2005
DOI: 10.1002/chem.200400689
|View full text |Cite
|
Sign up to set email alerts
|

An NMR and Molecular Modeling Study of Carbosilane‐Based Dendrimers Functionalized with Phenolic Groups or Titanium Complexes at the Periphery

Abstract: Dendrimers are modified polymers whose architecture is defined by the presence of a central atom or core with multiple branches. These molecules lend themselves to a variety of architectures and uses, including drug delivery and catalysis. The study of the molecular conformations and shapes of dendritic molecules is necessary but not yet routine. Here we present an NMR and molecular modeling study of a series of carbosilane dendrimers, namely 1G-{(CH2)3[C6H3(OMe)]OH}4 (1), 2G-{(CH2)3[C6H3(OMe)]OH}8 (2), and 2G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…From a structural point of view, this variation of T 2 reflects the different mobility and relative density distribution within the dendrimers, and this could be better defined if a more complete study, covering several signals, and not only T 2 , but also spin−lattice relaxation times ( T 1 ), were carried out (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…From a structural point of view, this variation of T 2 reflects the different mobility and relative density distribution within the dendrimers, and this could be better defined if a more complete study, covering several signals, and not only T 2 , but also spin−lattice relaxation times ( T 1 ), were carried out (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28] Another was using atomistic MD to model specific dendrimers, but still in implicit solvent or actual vacuum. Most notable are poly(propylene imine) (PPI) in vacuum [29,30] and melt [31,32] and poly(amido amine) (PAMAM) in vacuum [33][34][35] and melt, [36] but also various phenyl- [37][38][39][40] and carbosilane-based [41,42] dendrimers have been modelled. As both the solvent and the dendrimer composition influence the behaviour, explicit solvent atomistic simulations have also been performed for, e.g., PPI, [43][44][45][46] PAMAM [46][47][48][49] and carbosilane [50] dendrimers.…”
Section: Introductionmentioning
confidence: 99%
“…Metallodendrimer research has been steadily gaining ground during the past few years, and a considerable number of dendritic macromolecules containing transition metals at their core, branches, or periphery have been prepared for use in metal-based catalysis, including oligomerization and polymerization. , We have contributed to the chemistry of carbosilane dendrimers containing early-transition-metal complexes bonded to the dendritic periphery or focal point, usually through O- or N-donor anchoring ligands. , In our study of the catalytic performance in ethylene polymerization of nickel(II) complexes coordinated to carbosilane dendrimers through the pyridylimine ligands Ia − c (Chart ), we found that the microstructure and oligomer/polymer product distribution are significantly affected by the size of the dendritic precursor …”
Section: Introductionmentioning
confidence: 99%